Disparities in satisfaction among insured and uninsured adult outpatient department service users in Southern Ethiopia, 2022: a comparative cross-sectional study - Mulugeta Hailu Rad; Tekle Ejajo; Legesse Tesfaye Elilo; Selamu Abose Nedamo; Dawit Sullamo; Aklilu Habte Hailegebireal; Belay Erchafo (BMC, 2024)
Abstract Background Patient satisfaction is a critical measure of the quality of healthcare services provided by healthcare facilities. However, very few studies, particularly in Ethiopia, which includes the study area, have specifically examined these discrepancies among people who use outpatient care. In this study, satisfaction levels and associated factors were compared between insured and uninsured patients receiving outpatient services at public health institutions in Hadiya Zone, southern Ethiopia. Methods A facility-based comparative cross-sectional study design was employed on 630 patients using multistage and systematic random sampling. Data were collected using a pretested and structured interviewer-administered questionnaire. Results of the analysis were presented in text, tables, and graphs as appropriate. Multivariable logistic regression was used to predict associations between predictors and the outcome variable. Statistical significance was declared at p-value < 0.05. Results Overall, 344(55.48%) patients were satisfied with the service they received, of which 206(65.8%) out of 313 with a 95% CI [60.7-71.2%] were insured and 138(44.95%) out of 307 with a 95% CI [39.4-5.1%] were uninsured. Among insured patients, factors associated with higher satisfaction included having a family size less than five members [AOR = 3.3, 95% CI; 1.5, 7.4], perceived fair waiting time to be seen[AOR = 2.35, 95% CI; 1.02, 5.5], perceived short waiting time to be seen[AOR = 8.12, 95% CI; 1.6, 41.3], having all ordered laboratory tests available within the facility[AOR = 7.89, 95% CI; 3.5, 17.5], having some ordered laboratory tests within the facility[AOR = 2.97, 95% CI; 1.25, 7.01] having all prescribed medications available within the facility[AOR = 16.11, 95% CI; 6.25, 41.5], having some prescribed medications available within the facility[AOR = 13.11, 95% CI; 4.7, 36.4]. Among non-insured patients, factors associated with higher satisfaction included urban residency, a fair and short perceived time to be seen, having ordered laboratory tests within the facility, and having prescribed drugs within the facility. Conclusion This study identified lower overall satisfaction, particularly among uninsured patients. Enrollment in the CBHI program significantly impacted satisfaction, with both groups reporting lower levels compared to enrollment periods. Access to essential services, wait times, and socio-demographic factors identified as associated factors with patient satisfaction regardless of insurance status.